THE EFFECT OF LIQUID ORGANIC FERTILIZER OF ALOE VERA (Aloe vera L.) AND COFFEE GROUNDS ON THE GROWTH AND YIELD OF CAYENNE PEPPER PLANTS (Capsicum frutescens L.) - Zahrah, Nurindah; Palenewen, Evie; Maasawet, Elsje Theodora (Universitas Tanjungpura, 2024)
This research aims to determine the effect of liquid organic fertilizer from aloe vera (Aloe vera L.) and coffee grounds on the growth and yield of cayenne pepper plants (Capsicum frutescens L.). The type of research used by researchers is experimental research with a Randomized Group Factorial Design (RGFD). The samples used were 75 cayenne pepper (Capsicum frutescens L.) seeds of the Bara variety. The observation parameters used in this research were plant height (cm), number of leaves (strands), and plant fresh weight (grams). The results of data analysis showed that there was no effect of liquid organic fertiIizer from aloe vera (Aloe vera L.) and coffee grounds on the growth and yield of cayenne pepper plants (Capsicum frutescens L.). In the plant height parameter is smaller than , namely 1,070 1,85 at the age of 14 DAP, 0,978 1,85 at the age of 28 DAP, 1,747 1,85 at the age of 42 DAP, 1,373 1,85 at the age of 56 DAP, 1,238 1,85 at age 70 DAP, and 1,096 1,85 at age 84 DAP. In the number of leaves parameter is smaller than 0,738 1,85 at the age of 14 DAP, 1,059 1,85 at the age of 28 DAP, 0,981 1,85 at the age of 42 DAP, 0,833 1,85 at the age of 56 DAP, 0,154 1,85 at age 70 DAP, and 0,798 1,85 at age 84 DAP. In the fresh fruit weight parameter, is smaller than for 84 DAP, namely 0,798 1,85.